Ask Question
11 June, 08:49

The function h (x) = x2 + 3 and g (x) = x2 - 6. If g (x) = h (x) + k, what is the value of k?

+2
Answers (1)
  1. 11 June, 08:56
    0
    -9

    Step-by-step explanation:

    Think intuitively. The expression "g (x) = h (x) + k" simply means x^2 - 6 is equal to (x^2 + 3) plus a number. The only number changing is the constant value, and in order to go from 3 to - 6, we subtract - 9;

    x^2 - 6 = (x^2 + 3) - 9
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “The function h (x) = x2 + 3 and g (x) = x2 - 6. If g (x) = h (x) + k, what is the value of k? ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers